Evaluation of inter-observer variation for computed tomography identification of childhood interstitial lung disease. Issue 3 (29th July 2019) - Jacob, Joseph; Owens, Catherine M.; Brody, Alan S.; Semple, Thomas; Watson, Tom A.; Calder, Alistair; Garcia-Peña, Pilar; Toma, Paolo; Devaraj, Anand; Walton, Henry; Moreno-Galdó, Antonio; Aurora, Paul; et al.
Interstitial lung diseases (ILDs) that present in childhood (chILD) are seen far less frequently than ILDs presenting in adults which themselves constitute rare disorders [1]. Histopathological [2, 3] and imaging [4] characterisation of chILD disease subtypes therefore lags behind adult ILDs. The field has also been constrained by comparisons with disease morphology in adults, despite the developmental differences in terms of growth and healing in the paediatric lung, which may alter disease patterns and distributions. The American Thoracic Society [5] and European [1] chILD management guidelines both specify a pivotal role for computed tomography (CT) imaging in the work-up of chILD patients to: 1) determine whether a chILD is present or not; and 2) where possible, to make a specific diagnosis of the underlying cause. For the second aim to be achieved, diagnostic reviews need to be reproducible between experts. Our study uniquely examined agreement between observers of varying experience in the CT evaluation of chILD to inform whether the current status of CT imaging and knowledge can be diagnostic of specific chILDs. We hypothesised that observer agreement for chILD groups and diagnoses would be limited. The study was not designed to relate CT agreement to final diagnosis. As a secondary analysis, we examined how CT interpretation differed between observers in children under and over 2 years of age. Making chILD diagnoses on CT is poorly reproducible, even amongst sub-specialists. CT might best improve diagnostic confidence in a multidisciplinary team setting when augmented with clinical, functional and haematological results. http://bit.ly/327jRCw